Тартюф, или Обманщик: пьеса / Ж. Б. Мольер - Мольер Жан Батист (Школьная библиотека, 1989)
Экземпляры: БС (20170802) / Инвентарный номер: РТШ47906 / Сис.шифр: И(Фр) / Авт.знак: М 76 / ГРНТИ: 17 / ББК: 84(4/8)